2004
DOI: 10.1002/adma.200306355
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Enhancements in Toughness of Polyvinylidene Fluoride Nanocomposites via Nanoclay‐Directed Crystal Structure and Morphology

Abstract: Addition of nanoclays or other nanoparticles into various polymers to produce nanocomposites has been extensively utilized in an attempt to enhance the mechanical, physical, and thermal properties of polymers. While some interesting properties have been demonstrated, the resulting nanocomposites have yet to realize their full potential. Nanoparticles in general, and nanoclays in particular, with their nanometer size, high surface area, and the associated predominance of interfaces in the nanocomposites, can fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
352
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(372 citation statements)
references
References 25 publications
17
352
3
Order By: Relevance
“…Alternatively, a mechanism in analogy to that developed for the epitaxial crystallization of β modification on KBr substrate has been proposed [31]. The mechanism highlights the geometrical similarities between the crystal lattice of the inorganic phase (KBr, clay) and the β phase of PVDF [17,32]. It should be noted that the β modification was also found to be favored in the presence of Ag nanoparticles [33], functionalized multiwall carbon nanotubes [34] and functionalized graphene sheets [35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, a mechanism in analogy to that developed for the epitaxial crystallization of β modification on KBr substrate has been proposed [31]. The mechanism highlights the geometrical similarities between the crystal lattice of the inorganic phase (KBr, clay) and the β phase of PVDF [17,32]. It should be noted that the β modification was also found to be favored in the presence of Ag nanoparticles [33], functionalized multiwall carbon nanotubes [34] and functionalized graphene sheets [35].…”
Section: Methodsmentioning
confidence: 99%
“…Dramatic enhancements in toughness have been reported for a limited number of clay based nanocomposite systems including PVDF [17] and PVDF based blends [39]. In general, nanofillers homogeneously dispersed in a polymer matrix, in addition to inducing changes in crystallinity (both degree and type of phase) can give rise to a percolated network that has a protective role against the onset of catastrophic cracking; the load transfer efficiency largely depends upon the interfacial nanofiller/polymer shear stress [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, it has been reported that addition of clay platelets into PVDF polymer matrix induces polar crystalline phase 12,[18][19][20][21][22][23][24] . Priya and Jog [18][19][20] reported the effectiveness of organically modified montmorillonite for the induction of β polymorph formation in PVDF films.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been proposed and implemented [11][12][13][14] to increase the β phase content of PVDF films; however high temperature mechanical stretching and high voltage poling using are proved to be efficient and practical [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%